Modified lithium iron phosphate positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611010725.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-08
AI Technical Summary
首先,传统碳包覆(如采用沥青、蔗糖等碳源)在高温裂解后易形成不均匀、不连续的碳层,导致部分活性物质未被有效覆盖,且碳层与材料颗粒间的界面接触电阻较高,限制了电子传导效率的全面提升
本发明通过一种改性剂,同时解决了电子传导(粉阻、界面阻)、离子传导(均匀薄层)和结构稳固性(交联网络)多个维度的难题,实现了对磷酸铁锂材料综合电化学性能的协同提升,为制造低成本、高功率的动力与储能电池提供了关键材料基础。
Smart Images

Figure CN122501843B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, and particularly relates to a modified lithium iron phosphate cathode material, its preparation method, and its application. Background Technology
[0002] Although lithium iron phosphate (LiFePO4) cathode materials have advantages in safety and cycle life, their inherent low electronic conductivity and slow lithium-ion diffusion rate severely limit the fast charging (high rate) performance of batteries.
[0003] To address this challenge, the industry widely employs carbon coating and particle nanofiber technology. However, existing technologies have significant shortcomings: First, traditional carbon coating (such as using carbon sources like pitch and sucrose) tends to form uneven and discontinuous carbon layers after high-temperature pyrolysis, resulting in some active substances not being effectively covered. Furthermore, the interfacial contact resistance between the carbon layer and the material particles is high, which limits the overall improvement of electron conduction efficiency.
[0004] Secondly, while nanoparticles shorten the ion diffusion path, the rapid increase in the specific surface area of the material leads to a significant enhancement of the contact points and interface effects between particles. This results in a sharp increase in the powder resistance of the material during electrode preparation, which in turn hinders the macroscopic transport of electrons.
[0005] Therefore, existing modification methods are unable to achieve synergistic optimization among low powder resistivity, high ionic conductivity, and high electronic conductivity, which has become a key bottleneck restricting further breakthroughs in the rate performance of lithium iron phosphate materials. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the background art above, and to provide a high-rate, low-resistance modified lithium iron phosphate cathode material, its preparation method and application.
[0007] To solve the above-mentioned technical problems, the technical solution proposed by this invention is as follows: A method for preparing a modified lithium iron phosphate cathode material includes the following steps: (1) Lithium carbonate, iron phosphate, carbon source and water are mixed and ground, and then spray dried to obtain precursor powder; The carbon source is a glucose and an APEG-based composite polymer, with the mass ratio of the APEG-based composite polymer to glucose being 5:95 to 30:70. The APEG-based composite polymer is obtained by copolymerizing monomers a and b with APEG; monomer a is selected from acrylic acid and / or hydroxyethyl acrylate; monomer b is acrylonitrile. (2) The precursor powder is sintered under a protective atmosphere to obtain modified lithium iron phosphate cathode material.
[0008] Furthermore, the APEG-based composite polymer is an APEG-AA-AN copolymer formed by copolymerizing APEG, acrylic acid, and acrylonitrile.
[0009] Furthermore, the preparation method of the APEG-AA-AN copolymer includes: under inert gas protection, at a temperature of 85~95°C, adding a monomer mixture containing APEG, acrylic acid and acrylonitrile and an initiator solution dropwise into water, and maintaining the temperature for 2~3 hours.
[0010] Furthermore, the mass ratio of APEG, acrylic acid, and acrylonitrile is 6:3:1.
[0011] Furthermore, the molecular weight of APEG is 300~1000.
[0012] Furthermore, the total carbon content in the modified lithium iron phosphate cathode material is 1~2wt%.
[0013] Furthermore, the protective atmosphere is a mixture of nitrogen and hydrogen, with a nitrogen to hydrogen volume ratio of (92~98):(2~8).
[0014] Furthermore, the sintering process is as follows: heat to 300℃-400℃ and hold for 3-4 hours; then heat to 650℃-760℃ and hold for sintering for 8-12 hours.
[0015] The present invention also provides a modified lithium iron phosphate cathode material, which is prepared by the preparation method described above.
[0016] The present invention also provides a lithium-ion battery comprising the modified lithium iron phosphate cathode material described above.
[0017] This invention aims to overcome the shortcomings of existing lithium iron phosphate carbon coating technologies, such as uneven carbon layers, high interfacial contact resistance, and high nanoparticle powder resistance. By introducing a specific APEG (allyl polyethylene glycol)-based composite polymer as a partial carbon source, and using it in conjunction with a traditional carbon source (glucose), a composite carbon layer with high conductivity, excellent interfacial bonding, and particle bridging function is constructed on the surface of LiFePO4 particles. This simultaneously improves the electronic conductivity and lithium-ion diffusion rate of the material, and significantly reduces its powder resistance, ultimately obtaining a high-performance, high-rate lithium iron phosphate cathode material.
[0018] Compared with traditional pure glucose carbon coating technology, this invention introduces APEG-based composite polymers as an auxiliary carbon source, resulting in a significant synergistic effect. Its beneficial effects are specifically and prominently reflected in the following aspects: (1) Significantly reduce material resistance and optimize electrode conductive network Significantly reduced powder resistivity: After carbonization, the long-chain molecular structure of the APEG-based polymer can form robust "conductive carbon bridges" between adjacent LiFePO4 nanoparticles, fundamentally improving point-to-point electron transport between particles. Experimental results show that the powder resistivity of the lithium iron phosphate material obtained in this invention can be reduced by 20% to 50% compared to traditional pure glucose-coated samples.
[0019] Reduced interfacial contact resistance: The polymer achieves strong adsorption to the surface of LiFePO4 particles through its hydrophilic segments, forming a more uniform and denser coating layer. This significantly reduces poor contact between the carbon layer and the active material, effectively lowering the interfacial contact resistance between them.
[0020] (2) Maximize battery rate performance to achieve high-rate charging and discharging. Due to the higher electronic conductivity and optimized ion migration channels of the composite carbon layer, polarization of the battery at high rates is significantly suppressed. Batteries assembled using the materials of this invention maintain a capacity retention rate (relative to 0.1C capacity) of over 85% at a high charge-discharge rate of 5C, which is superior to that of conventional materials (typically below 80%). (3) Synergistic optimization, one dose with multiple effects This invention solves multiple challenges in electronic conduction (powder resistance, interfacial resistance), ion conduction (uniform thin layer), and structural stability (cross-linked network) simultaneously through a modifier, achieving a synergistic improvement in the comprehensive electrochemical performance of lithium iron phosphate materials and providing a key material foundation for manufacturing low-cost, high-power power and energy storage batteries. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is the infrared spectrum of APEG-AA-AN from Example 1; Figure 2 This is a SEM image of the cathode material in Example 4; Figure 3 This is a SEM image of the cathode material in Comparative Example 1; Figure 4 This is a TEM image of the cathode material in Example 4; Figure 5 It is the electrical performance EIS diagram; Figure 6 It is a ratio curve. Detailed Implementation
[0023] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0024] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0025] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0026] In some specific embodiments, the preparation method of the modified lithium iron phosphate cathode material of the present invention introduces an APEG (allyl polyethylene glycol)-based composite polymer as an auxiliary carbon source during the mixing process of lithium iron phosphate precursor and main carbon source glucose, forming a continuous nitrogen-doped carbon layer and interparticle conductive carbon bridges, thereby simultaneously reducing the interface resistance and powder resistance.
[0027] The APEG-based composite polymer is synthesized by copolymerizing APEG with the following monomers and / or their derivatives: Hydrophilic and interface-modifying monomers: selected from one or more of acrylic acid (AA) and hydroxyethyl acrylate (HEA). These monomers provide hydrophilic segments, enhancing the adsorption and binding of the polymer to the surface of LiFePO4 precursor particles.
[0028] High carbonization rate and conductive monomer: selected from acrylonitrile (AN). After high-temperature carbonization, this monomer can form an aromatic ring structure with high nitrogen content, which significantly improves the graphitization degree and electronic conductivity of the final carbon layer.
[0029] The synergistic mechanism of this invention is as follows: Uniform coating and strong interfacial bonding: The long-chain polyether structure and hydrophilic monomer segments of APEG give the polymer excellent dispersibility and wettability in aqueous precursors. It can be tightly adsorbed onto the surface of LiFePO4 particles through hydrogen bonds, coordination bonds, and other forces, forming a uniform pre-coating layer. This lays the foundation for the subsequent formation of a continuous, defect-free carbon layer and reduces the interfacial contact resistance between the carbon layer and the active material.
[0030] Constructing "particle conductive bridges": The long-chain molecular structure of this polymer can act as "molecular bridges" between adjacent LiFePO4 nanoparticles. After carbonization, these "bridges" transform into conductive carbon chains, effectively connecting isolated particles and constructing additional electronic conduction paths throughout the electrode material, thereby significantly reducing the powder resistance of the material.
[0031] Optimize the carbon layer structure and composition: Glucose serves as the main carbon source, providing the basic carbon skeleton. In the introduced APEG-based polymer, the nitrogen doping introduced by the acrylonitrile unit can effectively improve the intrinsic conductivity of the carbon layer. The crosslinking monomer ensures the integrity of the structure during carbonization, preventing the carbon layer from shrinking or breaking, and ultimately generating a nitrogen-doped composite carbon coating layer with higher graphitization and a more stable structure.
[0032] The present invention achieves the following effects: Synergistic effect and comprehensive performance improvement: Through the synergistic carbonization of glucose and APEG-based composite polymers, a "1+1>2" effect is achieved. While maintaining the advantages of mature and low-cost glucose carbon source technology, this invention utilizes a small amount of functional polymers to achieve a leapfrog improvement in rate performance and resistivity characteristics.
[0033] Significantly reduced powder resistance: The "particle conductive bridge" structure formed after the carbonization of APEG-based polymer fundamentally improves the electron transport efficiency between nanoparticles, resulting in a powder resistance of lithium iron phosphate material that is more than 20% lower than that of traditional pure glucose-coated samples.
[0034] Superior high-rate performance: Due to the higher conductivity and better ion transport channels of the composite carbon layer, batteries assembled using the materials of this invention exhibit excellent high-rate charge and discharge capabilities. For example, at a high rate of 5C, its discharge capacity retention (relative to 0.1C capacity) can be increased to over 85%, far superior to that of conventional materials (typically below 80%).
[0035] Good process compatibility and easy industrialization: This APEG-based polymer is water-soluble or has good dispersibility, and is highly compatible with existing glucose-based wet processes such as liquid-phase mixing and spray drying. It does not require major modifications to existing production lines, making it easy to scale up production and promote its application.
[0036] In some embodiments, the APEG-based composite polymer is an APEG-AA-AN copolymer. Its preparation method includes: under inert gas protection, at a temperature of 85-95°C, adding a monomer mixture (APEG, acrylic acid, acrylonitrile) and an initiator solution dropwise into water, and maintaining the temperature for 2-3 hours.
[0037] In some embodiments, the molecular weight of APEG is 300-1000. The mass ratio of APEG, acrylic acid, and acrylonitrile is (5-8):(2-4):1, preferably 6:3:1.
[0038] In some embodiments, the preparation method of the modified lithium iron phosphate cathode material of the present invention includes the following steps: (1) Lithium carbonate, iron phosphate, carbon source and water are mixed and ground, and then spray dried to obtain precursor powder.
[0039] In some embodiments, the carbon source is a glucose and APEG-based composite polymer, wherein the mass ratio of the APEG-based composite polymer to glucose is 5:95 to 30:70, preferably 10:90 to 20:80. The mass ratio of the total carbon source to iron phosphate is preferably 11:89. Lithium carbonate and iron phosphate are added in a molar ratio of 1:1, or in a slight excess of lithium carbonate.
[0040] (2) The precursor powder was sintered under a protective atmosphere to obtain modified lithium iron phosphate cathode material.
[0041] In some embodiments, the protective atmosphere is a mixture of nitrogen and hydrogen, with a nitrogen to hydrogen volume ratio of (92~98):(2~8).
[0042] In some embodiments, the sintering process is as follows: the temperature is increased to 300℃-400℃ at a rate of 2~4℃ / min, and held for 3~4 hours to fully decompose the organic matter; then the temperature is increased to 650℃-760℃ at a rate of 4~8℃ / min, and sintered at this temperature for 8~12 hours.
[0043] Example 1: Synthesis of APEG-AA-AN copolymer Raw materials: allyl polyethylene glycol (APEG, Mn=300-1000), acrylic acid (AA), acrylonitrile (AN), ammonium persulfate (APS, initiator), deionized water.
[0044] Synthesis steps: Add 100g of deionized water to a four-necked flask equipped with a stirrer, condenser and thermometer, purge with nitrogen for protection, stir and heat to 85-95℃.
[0045] The monomer mixture (60g APEG, 30g acrylic acid, 10g acrylonitrile) and the initiator solution (1.5g ammonium persulfate dissolved in 20g water) were slowly added dropwise simultaneously to the reaction flask through two constant pressure dropping funnels, with the dropping time controlled at 2-3 hours.
[0046] After the addition is complete, continue the reaction at 85-95℃ for 2-3 hours.
[0047] After the reaction was completed, the mixture was cooled to room temperature to obtain a pale yellow transparent liquid, which is an aqueous solution of APEG-AA-AN copolymer with a solid content of 40±2% and a pH of 6.5–7.5. This solution was directly used for the subsequent synthesis of lithium iron phosphate.
[0048] Product characterization: FT-IR characteristic peak: 3400 cm⁻¹ -1 (-OH), 2920 / 2850 cm -1 (-CH2-), 2240 cm -1 (-CN), 1730 cm -1 (C=O), 1650 cm -1 (Carboxyl group), 1100 cm -1 (COC), such as Figure 1 .
[0049] Example 2: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0050] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of carbon source (glucose and APEG-AA-AN) copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 5:95. Mix lithium carbonate, iron phosphate, all carbon source and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0051] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0052] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0053] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0054] Example 3: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0055] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of glucose and APEG-AA-AN copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 10:90. Mix lithium carbonate, iron phosphate, all carbon sources and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0056] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0057] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0058] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0059] Example 4: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0060] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of glucose and APEG-AA-AN copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 15:85. Mix lithium carbonate, iron phosphate, all carbon sources and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0061] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0062] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0063] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0064] Example 5: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0065] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of glucose and APEG-AA-AN copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 20:80. Mix lithium carbonate, iron phosphate, all carbon sources and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0066] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0067] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0068] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0069] Example 6: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0070] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of glucose and APEG-AA-AN copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 25:75. Mix lithium carbonate, iron phosphate, all carbon sources and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0071] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0072] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0073] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0074] Example 7: Preparation of high-rate, low-resistivity modified lithium iron phosphate materials Raw materials: ferric phosphate (FePO4·2H2O), lithium carbonate (Li2CO3), glucose (C6H2O) 12 O6), an aqueous solution of the APEG-AA-AN copolymer synthesized in Example 1.
[0075] Preparation steps: Mixing: Weigh lithium carbonate and iron phosphate according to the lithium:Fe molar ratio of Li:Fe = 1.05:1. The mass ratio of glucose and APEG-AA-AN copolymer to iron phosphate is 11:89, and the mass ratio of APEG-AA-AN copolymer to glucose (on a solid basis) is 30:70. Mix lithium carbonate, iron phosphate, all carbon sources and deionized water to prepare a slurry with a solid content of 30%, and grind it in a sand mill for 1 hour.
[0076] Precursor treatment: The above slurry is spray-dried to obtain a uniform precursor powder.
[0077] Sintering: The precursor powder was placed in a tube furnace and sintered under a nitrogen / hydrogen (volume ratio 95:5) protective atmosphere. The sintering procedure was as follows: the temperature was increased to 350°C at a rate of 3°C / min and held for 3 hours to fully decompose the organic matter; then the temperature was increased to 700°C at a rate of 5°C / min and sintered at this temperature for 8 hours.
[0078] Post-processing: After sintering, the material is naturally cooled to room temperature. The resulting block material is then crushed and sieved to obtain the carbon-coated lithium iron phosphate cathode material of this embodiment, denoted as LFP-APEG.
[0079] Comparative Example 1: Traditional glucose-coated lithium iron phosphate materials The preparation method was exactly the same as in Example 4, except that glucose was used as the carbon source throughout, instead of the APEG-AA-AN copolymer. The mass of the APEG-AA-AN copolymer was replaced with an equal amount of glucose. This sample was designated LFP-Glucose.
[0080] Comparative Example 2: Using only APEG-based composite polymers, without glucose The carbon source was 100% APEG-AA-AN copolymer, and the rest was the same as in Example 4.
[0081] Comparative Example 3: Using only pure APEG monomers, without copolymerization Carbon source = 85% glucose + 15% pure APEG (without AA / AN copolymer), the rest is the same as in Example 4.
[0082] Material characterization Figure 2 This is a SEM image of the cathode material in Example 4; Figure 3 This is a SEM image of the cathode material in Comparative Example 1. It can be seen that: the carbon layer in Comparative Example 1 is discontinuous, the particles are exposed, and there is obvious agglomeration; while in Example 4, the particles are uniformly dispersed, the carbon layer is continuous and dense, and the surface is intact.
[0083] Figure 4 This is a TEM image of the cathode material in Example 4. It can be seen that the LFP surface has a continuous, uniform, and flat carbon layer with a thickness of about 5-10 nm.
[0084] Performance testing 1. Use a four-probe powder resistance meter or compact it using a specific mold (e.g., 4T / cm). 2 After applying pressure, its resistance is measured.
[0085] 2. Electrochemical performance testing (rate performance): Using the materials from the examples and comparative examples as the positive electrode and lithium metal as the negative electrode, CR2032 coin cells were assembled. Charge-discharge tests were conducted at different rates (voltage range 2.5V-4.2V) on the Blue Electric testing system.
[0086] The performance test results are shown in Table 1-2.
[0087] Table 1. Properties of APEG-AA-AN copolymers with different addition amounts
[0088] Table 2 Performance of Examples and Comparative Examples
[0089] It can be seen that the optimal addition ratio of APEG-AA-AN is 10%~20%. Glucose and APEG copolymer have a synergistic effect, jointly reducing electrical resistance and improving capacity retention. Moreover, the effects of this invention can only be achieved through copolymerization of APEG and AA / AN.
[0090] Figure 5 The electrical performance EIS diagrams (comparative examples 3, 2, 1, and 4) show that example 4 has the smallest interface transfer resistance. Figure 6 These are the magnification curves (comparative examples 3, 2, 1, and 4), showing that example 4 has the highest magnification performance.
[0091] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Therefore, any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention should fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified lithium iron phosphate cathode material, characterized in that, Includes the following steps: (1) Lithium carbonate, iron phosphate, carbon source and water are mixed and ground, and then spray dried to obtain precursor powder; The carbon source is a glucose and an APEG-based composite polymer, with the mass ratio of the APEG-based composite polymer to glucose being 5:95 to 30:
70. The APEG-based composite polymer is an APEG-AA-AN copolymer formed by copolymerizing APEG, acrylic acid, and acrylonitrile; (2) The precursor powder is sintered under a protective atmosphere to obtain modified lithium iron phosphate cathode material.
2. The method for preparing the modified lithium iron phosphate cathode material according to claim 1, characterized in that, The preparation method of the APEG-AA-AN copolymer includes: under inert gas protection, at a temperature of 85~95°C, adding a monomer mixture containing APEG, acrylic acid and acrylonitrile and an initiator solution dropwise into water, and maintaining the temperature for 2~3 hours.
3. The method for preparing the modified lithium iron phosphate cathode material according to claim 2, characterized in that, The mass ratio of APEG, acrylic acid, and acrylonitrile is 6:3:
1.
4. The method for preparing the modified lithium iron phosphate cathode material according to claim 2, characterized in that, APEG has a molecular weight of 300~1000.
5. The method for preparing the modified lithium iron phosphate cathode material according to claim 1, characterized in that, The total carbon content in the modified lithium iron phosphate cathode material is 1~2wt%.
6. The method for preparing the modified lithium iron phosphate cathode material according to claim 1, characterized in that, The protective atmosphere is a mixture of nitrogen and hydrogen, with a nitrogen to hydrogen volume ratio of (92~98):(2~8).
7. The method for preparing the modified lithium iron phosphate cathode material according to claim 1, characterized in that, The sintering process is as follows: heat to 300℃-400℃ and hold for 3-4 hours; then heat to 650℃-760℃ and hold for sintering for 8-12 hours.
8. A modified lithium iron phosphate cathode material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.
9. A lithium-ion battery, characterized in that, It comprises the modified lithium iron phosphate cathode material as described in claim 8.
Citation Information
Patent Citations
Method for preparing composite iron-based polyanion positive electrode material
CN119637832A
Multifunctional carbon source, preparation method and application thereof, carbon-coated lithium iron phosphate main material, preparation method of carbon-coated lithium iron phosphate main material, and lithium ion battery
CN122302137A